Pruning effect on peach palm (Bactris gasipaes Kunth) transplanting. - Arroyo-Oquendo, Carlos (2006)
Five treatments combining differentpruning practices of foliage and roots were conducted. Theirbehaviour was evaluated six months after transplanting to thefield, based on seven different parameters. All weretransplanted with naked roots. A comparative evaluation wasdone based on the external visual presence or absence of thenew emerging leaf or guide leaf. The results were as follows:the plants that were not pruned, were statiscally superior to allpruning treatments tried, not only in survival percentage(90.33%) but also in the other six variables studied, mainly inregard to the development of the plant measured by the totalweight recorded six months after the transplanting. Theplants with no foliage and no roots showed 63.33% ofsurvival and their posterior recovery, as measured by theweight of the roots and aerial part of the plant, was markedlyinferior to all other treatments. In all cases, including thecontrol plots, the presence of the new emerging leaf meant a2 to 4% increase in the survival of the plants. The sevenvariables used were highly correlated: plant diameter andheight, number of leaves, root system and aerial part weight,total plant weight, and survival percentage.